Brachymetatarsia: Surgical Management, Case Report, and Literature Review - David Zhu; Maxime Lefèvre; Andréa Fernandez; Laurent Galois (Case Reports in Orthopedics)
Background. Brachymetatarsia is defined by an abnormal shortening of the metatarsal bone. This rare condition is mostly primary and congenital. Consequences of this malformation are both esthetic and functional, due to pain and mechanical problems in the forefoot. Surgical management is an important part of patient care. There are two main options: gradual lengthening by progressive callotosis distraction using an external fixator and one stage lengthening using bone graft and osteotomy of the bone. This review presents two cases using the one stage lengthening surgical management method. We also discuss some reports in the literature with the aim to compare the advantages and disadvantages of the two surgical methods. Literature concerning the surgical management of brachymetatarsia was identified using the PubMed and Google Scholar databases. Patient Presentation. We describe two female patients aged 20 and 26 years who underwent one stage lengthening surgery of the fourth toe with isolated brachymetatarsia using an iliac bone graft and internal fixator plate. The two patients had a lengthening of around 10 mm after postoperative evaluation. No skin complications were noted, but one of the patients reported flexor stiffness after surgery. Concerning the functional and cosmetic aspects, the two patients are satisfied with the management. Conclusions. In the literature, one stage lengthening seems to be the most favorable option for the care of brachymetatarsia. Studies show a short healing time and fewer complications like infection, stiffness, malalignment, and malunion. Some reviews note the utility of the gradual lengthening of severe brachymetatarsia when a longer lengthening is necessary. There is no definite consensus concerning the management of brachymetatarsia.